Future time perspective and turnover intention: The mediating role of resilience - Indirasari, Dyah Triarini; Purba, Debora Eflina; Anindita, Rizka (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
The intention of employees to leave the organization, or known as turnover intention, is something that must be taken seriously by an organization as it may affect the sustainability of the organization. This study aimed to determine the effect of resilience as a mediator in the relationship between future time perspective (FTP) and turnover intention. Data were taken using convenience sampling from various state-owned enterprises (Badan Usaha Milik Negara, BUMN) in Depok and Jakarta area (N = 310). The study used a self-rating method using 3 measurements, namely Zimbardo Time Perspective Inventory, Brief Resilience Scale, and Turnover Intention. Data were analyzed using mediation technique by Hayes’ PROCESS macro on SPSS program. The results showed that FTP negatively and significantly affected turnover intention and that resilience fully mediated the relationship. As a practical implication, this study provides information for organizations to employ programs to increase employees’ future time perspective and resilience.